Fast pyrolysis of date palm biomass using Py-GCMS. (December 2021) - Bensidhom, Gmar; Arabiourrutia, Miriam; Ben Hassen Trabelsi, Aïda; Cortazar, Maria; Ceylan, Selim; Olazar, Martin
Abstract: Pyrolysis of Date Palm Petiole (DPP) and Date Palm Seed (DPS) biomass was conducted by fast pyrolysis and on-line analysis of the outlet stream by gas chromatography connected to mass spectrometry (Py-GCMS) at different temperatures (450, 500 and 600 °C) in order to study the effect of this variable on the product distribution. The concentration of the components in the volatile stream (bio-oil and non-condensable gases) was greatly influenced by temperature and, to a minor extent, by the content of the biomass components (cellulose, hemicellulose and lignin). The most abundant compound families quantified are acids, anhydrosugars, ketones, furans and phenols. The most abundant compound identified was levoglucosan, which is mainly derived from the degradation of cellulose, with its relative content being as high as 18.3% for DPS pyrolysis at 450 °C and considerably lower for DPP pyrolysis (12.2%). The relative content of acetic acid was as higher as 10.2% at 450 °C for DPP pyrolysis. The knowledge of product composition is crucial for the development of large scale fast pyrolysis units for the valorization of these Tunisian agricultural wastes. Highlights: Bio-oil is of high quality for the production of value-added chemicals, fuels or H2 . Acids and anhydrosugars prevail, with the latter depending on biomass composition. Levoglucosan content sharply decreases with temperature in the 450–600 °C range. The content of acetic acid is closely related to the content of hemicellulose. Condensable fraction best use is for energy supply to the pyrolysis unit.